Partial ionic bonding in homogeneous sodium clusters - Kaware, Vaibhav; Joshi, Kavita (Condensed Matter Physics, 2015)
In this work, we report an interesting observation of partial ionic bonding due to charge transfer in homogeneous sodium clusters. The charge transfer causes the electronic charge to accumulate on the surface, and the resulting charges on atoms range between +0.4 to -1.0 |e^-|. We also demonstrate that this disparity among effective charges on atoms is geometry dependent, such that atoms experiencing similar surrounding, have equal effective charge. It is speculated that this phenomenon will occur among other homogeneous clusters as well, and its extent will be defined by the valence electron delocalization.

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Predicting the redox potentials of phenazine derivatives using DFT-assisted machine learning - Ghule, Siddharth; Dash, Soumya Ranjan; Bagchi, Sayan; Joshi, Kavita; Vanka, Kumar (ACS Omega, 2022)
This study investigates four machine-learning (ML) models to predict the redox potentials of phenazine derivatives in dimethoxyethane using density functional theory (DFT). A small data set of 151 phenazine derivatives having only one type of functional group per molecule (20 unique groups) was used for the training. Prediction accuracy was improved by a combined strategy of feature selection and hyperparameter optimization, using the external validation set. Models were evaluated on the external test set containing new functional groups and diverse molecular structures. High prediction accuracies of R2 > 0.74 were obtained on the external test set. Despite being trained on the molecules with a single type of functional group, models were able to predict the redox potentials of derivatives containing multiple and different types of functional groups with good accuracies (R2 > 0.7). This type of performance for predicting redox potential from such a small and simple data set of phenazine derivatives has never been reported before. Redox flow batteries (RFBs) are emerging as promising candidates for energy storage systems. However, new green and efficient materials are required for their widespread usage. We believe that the hybrid DFT-ML approach demonstrated in this report would help in accelerating the virtual screening of phenazine derivatives, thus saving computational and experimental costs. Using this approach, we have identified promising phenazine derivatives for green energy storage systems such as RFBs.

Pseudo-boehmite AlOOH supported NGr composite-based air electrode for mechanically rechargeable Zn-air battery applications - Kharabe, Geeta Pandurang; Manna, Narugopal; Nadeema, Ayasha; Singh, Santosh K.; Mehta, Shweta; Nair, Aathira; Joshi, Kavita; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2022)
Both mechanically and electrically rechargeable zinc-air batteries (ZABs) have received much interest due to their high energy density and suitability for mobile and stationary applications. However, their commercialization has been impeded by the lack of robust, low-cost and environmentally benign catalyst materials that can be easily scaled up. In this context, the present work introduces a new type of transition metal-free catalytic material (AlOOH/NGr) by anchoring the pseudo-boehmite phase of aluminium oxyhydroxide (AlOOH) nanosheets over nitrogen-doped graphene (NGr) via a single-step and straightforward hydrothermal process. Furthermore, density functional theory (DFT) based computation demonstrates that the nucleation of AlOOH starts from the N-sites and points towards the strong surface interaction between AlOOH and NGr via doped nitrogen. AlOOH/NGr consisting of thin layered pseudo-boehmite sheets uniformly distributed over NGr has displayed an oxygen reduction reaction onset potential of 0.83 V and a half-wave potential of 0.72 V, along with good catalytic durability in alkaline medium. With this, AlOOH/NGr, when used as an air electrode for fabricating a primary Zn-air battery, the system has exhibited an open circuit voltage of similar to 1.27 V with a flat discharge profile at a current rate of 10 mA cm(-2). The fabricated system delivered a specific capacity of similar to 720 mA h g(-1) and a high power density of 204 mW cm(-2) and is comparable to the counterpart system based on the state-of-the-art Pt/C (20 wt% Pt) cathode. Additionally, the homemade battery was able to maintain its performance after 4 times of mechanical recharging of the battery, which lasted for more than 35 h at a discharge current density of 10 mA cm(-2). Thus, we have uncovered the potential of an earth-abundant metal-based catalytic system for fabricating and demonstrating a robust mechanically rechargeable zinc-air battery.

Photoinduced CO2 and N2 reductions on plasmonically enabled gallium oxide - Ojha, Niwesh; Thakkar, Kavita; Bajpai, Abhinav; Joshi, Kavita; Kumar, Sushant (Journal of Colloid and Interface Science, 2023)
Ag-containing ZnO/ b-Ga2O3 semiconductor, which exhibit reduced bandgap, increased light absorption, and hydrophilicity, have been found to be useful for photocatalytic CO2 reduction and N2 fixation by water. The charge-separation is facilitated by the new interfaces and inherent vacancies. The Ag@GaZn demonstrated the highest photocurrent response, about 20-and 2.27-folds that of the Ga and GaZn sam-ples, respectively. CO, CH4, and H2 formed as products for photo-reduction of CO2. Ag@GaZn catalyst exhibited the highest AQY of 0.121 % at 400 nm (31.2 W/m2). Also, Ag@GaZn generated 740 lmolg-1 of NH4+ ions, which was about 18-folds higher than Ga sample. In situ DRIFTS for isotopic-labelled 13CO2 and 15N2 reaffirmed the photo-activity of as-synthesized catalysts. Density functional theory pro-vided insight into the relative affinity of different planes of heterostructures towards H2O, CO2 and N2 molecules. The structure-photoactivity rationale behind the intriguing Ag@GaZn sample offers a funda-mental insight into the role of plasmonic Ag and design principle of heterostructure with improved pho-toactivity and stability.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: CO2 reduction; DRIFTS density functional theory; hydrophilicity; Photocurrent response

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability